TNF blockers inhibit spinal radiographic progression in ankylosing spondylitis by reducing disease activity: results from the Swiss Clinical Quality Management cohort. Issue 1 (22nd September 2017) - Molnar, Christoph; Scherer, Almut; Baraliakos, Xenofon; de Hooge, Manouk; Micheroli, Raphael; Exer, Pascale; Kissling, Rudolf O; Tamborrini, Giorgio; Wildi, Lukas M; Nissen, Michael J; Zufferey, Pascal; Bernhard, Jürg; et al.
Abstract : Objectives: To analyse the impact of tumour necrosis factor inhibitors (TNFis) on spinal radiographic progression in ankylosing spondylitis (AS). Methods: Patients with AS in the Swiss Clinical Quality Management cohort with up to 10 years of follow-up and radiographic assessments every 2 years were included. Radiographs were scored by two readers according to the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) with known chronology. The relationship between TNFi use before a 2-year radiographic interval and progression within the interval was investigated using binomial generalised estimating equation models with adjustment for potential confounding and multiple imputation of missing values. Ankylosing Spondylitis Disease Activity Score (ASDAS) was regarded as mediating the effect of TNFi on progression and added to the model in a sensitivity analysis. Results: A total of 432 patients with AS contributed to data for 616 radiographic intervals. Radiographic progression was defined as an increase in ≥2 mSASSS units in 2 years. Mean (SD) mSASSS increase was 0.9 (2.6) units in 2 years. Prior use of TNFi reduced the odds of progression by 50% (OR 0.50, 95% CI 0.28 to 0.88) in the multivariable analysis. While no direct effect of TNFi on progression was present in an analysis including time-varying ASDAS (OR 0.61, 95% CI 0.34 to 1.08), the indirect effect, via a reduction in ASDAS, was statistically significant (OR 0.75, 95% CI 0.59 to 0.97). Conclusion: TNFis are associated with a reduction of spinal radiographic progression in patients with AS. This effect seems mediated through the inhibiting effect of TNFi on disease activity.